Structural, optical and magnetic studies of the thin films and nanoparticles of ZnCoO prepared by pulsed laser ablation - Stolyarchuk, Ihor; Kuzyk, Oleh; Stefanuik, Ireneusz; Dan'kiv, Olesya; Popovych, Andriy; Stolyarchuk, Andriy (Physics and Chemistry of Solid State, 2026)
Pulsed laser ablation has been applied for fabrication of Zn1-xCoxO thin films and nanostructures with a cobalt content of up to 10%. X-ray diffraction studies indicate that all samples are crystalised in a hexagonal wurtzite structure with a preferred orientation along the (002) plane. No other peaks corresponding to cobalt clusters or cobalt oxide were detected. Atomic forse microscopy (AFM) and scanning electron microscopy (SEM) was used for characterization of obtained samples. The energy bandgap decrease with an increase of Co dopant concentration, which is due to the exhibition of the s,p–d exchange interaction. In the long-wavelength region of the spectrum the additional absorption is observed, with are explained in terms of d–d transitions in tetrahedrally coordinated Co2+ ions. In photoluminescence spectra, four main peaks were revealed, which are ascribed to near band gap emission and nterstitial zinc, oxygen vacancies, and other impurities and defects, not only in the bulk but also on the surfaces of the investigated samples. Electron paramagnetic resonance studies have confirmed ferromagnetic ordering in Zn1-xCoxO thin films and nanoparticles at room temperatures. One of the most probable mechanisms for the origin of ferromagnetic ordering is the bound magnetic polaron model.